Cloning and expression of a xylanase xynB from Aspergillus niger IA‐001 in Pichia pastoris. (21st June 2013) - Fang, Wei; Gao, He; Cao, Yunhe; Shan, Anshan
<x xml:space="preserve">Abstract</x> The high‐level expression of the xylanase GH11 gene from Aspergillus niger IA‐001 called xynB was successfully completed in Pichia pastoris. The xynB gene encoding a mature xylanase of 225 amino acid was subcloned into the pPICZαA vector and was transformed into P. pastoris X‐33 under the control of the alcohol oxidase I (AOX1) promoter. The xynB gene was ligated with a sequence encoding modified α‐factor signal peptide (pPICZαmA) and the recombinant xylanase activity, which was measured 1280 U ml−1, was 1.5‐fold higher than when it was inserted into pPICZαA and was 19.39‐fold greater than the native xylanase in the original strain. In a 10 L fermenter, the recombinant xylanase activity measured 10, 035 U ml−1 after 114 h. The SDS–PAGE analysis revealed that the purified xynB protein migrated as a single band with an apparent molecular weight of 24 kDa. The specific activity, using beechwood xylan as a substrate, was 1916 U mg−1. The xylanase activity was optimal at pH 5.0 and at 50 °C. In addition, the xynB was active over a pH range of 2.2 to 10.0. The apparent Km and Vmax values were 4.429 mg ml−1 and 1429 U mg−1, respectively.